2013
DOI: 10.1371/journal.pone.0060116
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Evolution of the Histidine Triad Protein (HTP) Family in Streptococcus

Abstract: The Histidine Triad Proteins (HTPs), also known as Pht proteins in Streptococcus pneumoniae, constitute a family of surface-exposed proteins that exist in many pathogenic streptococcal species. Although many studies have revealed the importance of HTPs in streptococcal physiology and pathogenicity, little is known about their origin and evolution. In this study, after identifying all htp homologs from 105 streptococcal genomes representing 38 different species/subspecies, we analyzed their domain structures, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…Furthermore, such a recovery for strains lacking pht genes is also consistent with the Pht proteins not contributing to defense against Zn 2ϩ toxicity, as we found to be the case in vitro. In other streptococci, adcAII homologues are often found with only one pht gene in the genome (24). Given that we have shown that all four Pht proteins of S. pneumoniae have overlapping functionality with respect to aiding in delivery of Zn 2ϩ to AdcAII, it is not apparent what the advantage of producing four such proteins is, as opposed to perhaps simply producing a greater quantity of one Pht protein.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, such a recovery for strains lacking pht genes is also consistent with the Pht proteins not contributing to defense against Zn 2ϩ toxicity, as we found to be the case in vitro. In other streptococci, adcAII homologues are often found with only one pht gene in the genome (24). Given that we have shown that all four Pht proteins of S. pneumoniae have overlapping functionality with respect to aiding in delivery of Zn 2ϩ to AdcAII, it is not apparent what the advantage of producing four such proteins is, as opposed to perhaps simply producing a greater quantity of one Pht protein.…”
Section: Discussionmentioning
confidence: 86%
“…The overlapping roles of these zinc acquisition systems in S. agalactiae raise the question of the reason for the basis for the conservation of multiple zinc import pathways. Recently, it has been proposed that the Sht-family genes, which are frequently acquired as operons that also contain lmb and adcAII genes, were acquired prior to the emergence of the Streptococcus genus (10). As a consequence, maintenance or loss of Sht-family genes are presumed to arise from the competing selective pressures associated with their physiological function, such as zinc acquisition and evasion of host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple zinc-specific SBPs is an unusual feature largely unique to the streptococci, since most prokaryotes employ only a single protein. This appears to have arisen due to the ancient acquisition of a genetic element containing Lmb (or AdcAII) and a histidine triad (HT) protein in the streptococcal genus (10). Subsequent gene duplication events have led to the emergence of multiple copies of the histidine triad proteins and Lmb/AdcAII-type SBPs.…”
mentioning
confidence: 99%
“…Homologs of pht genes have been identified in the human pathogens Streptococcus pyogenes (17,18) and Streptococcus agalactiae (19), but also among commensal streptococcal species and in some nonstreptococcal species (20). In S. pyogenes, this type of protein has been identified as an adhesin binding to extracellular matrix protein type I collagen (21).…”
mentioning
confidence: 99%